Oral Treatment With Bisphosphonates of Osteoporosis Does Not Increase the Risk of Severe Gastrointestinal Side Effects: A Meta-Analysis of Randomized Controlled Trials - Dömötör, Zsuzsa Réka; Vörhendi, Nóra; Hanák, Lilla; Hegyi, Péter; Kiss, Szabolcs; Csiki, Endre; Szakó, Lajos; Párniczky, Andrea; Erőss, Bálint (Frontiers in Endocrinology, 2020)
Introduction: Bisphosphonates (BPs) are first-line therapy for osteoporosis. Adherence is usually low in chronic, asymptomatic diseases, but gastrointestinal (GI) side-effects can also contribute to low adherence in BP therapy and may necessitate a review by a gastroenterologist with or without gastroscopy. Aims: Our meta-analysis aims to determine the risk of severe GI adverse events due to oral BP therapy in osteoporotic patients. Methods: A systematic search was conducted in three databases up to September 2020 for randomized controlled trials (RCTs) detailing GI adverse events in adults with osteoporosis on BP compared to placebo. Risk ratios (RRs) with 95% confidence intervals (CI) were calculated for non-severe and severe adverse events indicating endoscopic procedure with the random-effects model. Statistical heterogeneity was assessed using chi2 and I2 statistics. Results: Forty-two RCTs with 39,047 patients with 9,999 non-severe and 1,503 severe GI adverse events were included. The incidence of non-severe and severe adverse events ranged between 0.3-54.9% and 0-10.3%, respectively. There was no difference between BP and control groups in terms of the risk of non-severe or severe side effects: RR=1.05 (CI: 0.98 – 1.12), I2=48.1%, and RR=1.01 (CI: 0.92 – 1.12), I2=0.0%, respectively. Subgroup analysis of the most commonly used BP, once-weekly alendronate 70 mg, revealed an association between bisphosphonates and the risk of non-severe GI adverse events, RR=1.16 (CI: 1.00 – 1.36), I2=40.7%, while the risk of severe GI side effects was not increased in this subgroup, RR=1.20 (CI: 0.83 – 1.74), I2=0.0%. Conclusion: Our results show that bisphosphonates do not increase the risk of severe GI adverse events. However, the marked variability of the screening for side effects in included studies limits the strength of evidence of our result. Another limitation is that in most of the studies included in the analysis GI diseases were exclusion criteria. The conclusions drawn from the meta-analysis are therefore restricted to selected populations, and the results must be interpreted with caution.